Exercise-training intervention studies in competitive swimming - Aspenes, S. T.; Karlsen, T. (Sports Medicine, 2012)
Competitive swimming has a long history and is currently one of the largest Olympic sports, with 16 pool events. Several aspects separate swimming from most other sports such as (i) the prone position; (ii) simultaneous use of arms and legs for propulsion; (iii) water immersion (i.e. hydrostatic pressure on thorax and controlled respiration); (iv) propulsive forces that are applied against a fluctuant element; and (v) minimal influence of equipment on performance. Competitive swimmers are suggested to have specific anthropometrical features compared with other athletes, but are nevertheless dependent on physiological adaptations to enhance their performance. Swimmers thus engage in large volumes of training in the pool and on dry land. Strength training of various forms is widely used, and the energetic systems are addressed by aerobic and anaerobic swimming training. The aim of the current review was to report results from controlled exercise training trials within competitive swimming. From a structured literature search we found 17 controlled intervention studies that covered strength or resistance training, assisted sprint swimming, arms-only training, leg-kick training, respiratory muscle training, training the energy delivery systems and combined interventions across the aforementioned categories. Nine of the included studies were randomized controlled trials. Among the included studies we found indications that heavy strength training on dry land (one to five repetitions maximum with pull-downs for three sets with maximal effort in the concentric phase) or sprint swimming with resistance towards propulsion (maximal pushing with the arms against fixed points or pulling a perforated bowl) may be efficient for enhanced performance, and may also possibly have positive effects on stroke mechanics. The largest effect size (ES) on swimming performance was found in 50 m freestyle after a dry-land strength training regimen of maximum six repetitions across three sets in relevant muscle-groups (ES 1.05), and after a regimen of resisted- and assisted-sprint training with elastic surgical tubes (ES 1.21). Secondly, several studies suggest that high training volumes do not pose any immediate advantage over lower volumes (with higher intensity) for swim performance. Overall, very few studies were eligible for the current review although the search strategy was broad and fairly liberal. The included studies predominantly involved freestyle swimming and, overall, there seems to be more questions than answers within intervention-based competitive swimming research. We believe that this review may encourage other researchers to pursue the interesting topics within the physiology of competitive swimming.